Establishment of a Seronegative Occult Infection With an Active Hepatitis B Virus Reservoir Enriched of Vaccine Escape Mutations in a Vaccinated Infant After Liver Transplantation. (14th August 2019) - Salpini, Romina; Pietrobattista, Andrea; Piermatteo, Lorenzo; Basso, Maria Sole; Bellocchi, Maria C; Liccardo, Daniela; Carioti, Luca; Francalanci, Paola; Aragri, Marianna; Alkhatib, Mohammed; Scutari, Rossana; Candusso, Manila; et al.
Abstract: We describe the establishment of a seronegative occult hepatitis B virus (HBV) infection (OBI) in a successfully vaccinated infant who underwent liver transplantation from an donor positive for antibody to hepatitis B core antigen (anti-HBc). The use of highly sensitive droplet digital polymerase chain reaction assays revealed a not negligible and transcriptionally active intrahepatic HBV reservoir (circular covalently closed DNA, relaxed circular DNA, and pregenomic RNA: 5.6, 2.4, and 1.1 copies/1000 cells, respectively), capable to sustain ongoing viral production and initial liver damage. Next-generation sequencing revealed a peculiar enrichment of hepatitis B surface antigen vaccine-escape mutations that could have played a crucial role in OBI transmission. This clinical case highlights the pathobiological complexity and the diagnostic challenges underlying OBI.